2008
DOI: 10.1007/s00442-008-1209-5
|View full text |Cite
|
Sign up to set email alerts
|

Understory plant diversity is related to higher variability of vegetative mobility of coexisting species

Abstract: Theoretical studies claim that if co-occurring species have very diVerent mobilities this will result in greater small-scale species richness, but empirical evidence is still lacking. We measured horizontal vegetative mobility (VM) of 48 herbaceous understory species and estimated small-scale species richness in early and late successional boreonemoral herb-rich coniferous forests in central Estonia. VM of erosulate growth forms was signiWcantly higher than that of hemi-rosette and rosette growth forms. Erosul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
1
33
1
Order By: Relevance
“…The results of some previous empirical studies have suggested that a trade-off in resource allocation between clonal spread (colonization ability) and individual ramet size (ramet-level competitive ability) could serve as a mechanism by which species coexistence could be achieved (Wildová et al 2007;Moora et al 2009). The ability of weaker competitors to rapidly exploit unoccupied, resource-rich habitat patches could also promote species coexistence, but this mechanism has been largely overlooked or confounded with colonization ability in previous studies (Pacala and Rees 1998;Bolker and Pacala 1999;Amarasekare 2003).…”
Section: Discussionmentioning
confidence: 96%
“…The results of some previous empirical studies have suggested that a trade-off in resource allocation between clonal spread (colonization ability) and individual ramet size (ramet-level competitive ability) could serve as a mechanism by which species coexistence could be achieved (Wildová et al 2007;Moora et al 2009). The ability of weaker competitors to rapidly exploit unoccupied, resource-rich habitat patches could also promote species coexistence, but this mechanism has been largely overlooked or confounded with colonization ability in previous studies (Pacala and Rees 1998;Bolker and Pacala 1999;Amarasekare 2003).…”
Section: Discussionmentioning
confidence: 96%
“…We found that older stages of forest regeneration were characterized by more clonal species with longer spacers, short-lived connections (splitting clones), and small below-ground bud banks, confirming our second hypothesis (H2). The percentage of explained variance by each axis is shown forest herb layer (Moola and Vasseur 2004;Godefroid et al 2005;Moora et al 2009). Furthermore, the contribution of weedy and invasive species is negligible in the mountainous landscape of the Apennines (Bartha et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For plants, this spatial movement occurs through vegetative growth or seed dispersal (here we use ''seed'' as a general term for a reproductive dispersing unit). While vegetative spread plays a great role in small-scale patterns of species distribution (Moora et al 2009), seed dispersal is a process that shapes local populations and communities as well as large-scale distribution of species (Levin et al 2003.…”
Section: Introductionmentioning
confidence: 99%